Pengaruh Indeks Pembangunan Manusia (IPM), Tingkat Pengangguran Terbuka (TPT) Dan Tingkat Kemiskinan Terhadap Laju Pertumbuhan Ekonomi : Studi Kasus Di Pulau Kalimantan Tahun Periode 2014-2023 - Putri Wulan Sari; Miftahul Habib; Refta Ardiansyah; Muhammad Kurniawan (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to analyze the influence of the Human Development Index (HDI), Open Unemployment Rate (TPT) and Poverty Rate (TK) on the Rate of Economic Growth on Kalimantan Island in 2014-2023. The independent variables are the Human Development Index (HDI), Open Unemployment Rate (TPT) and Poverty Rate (TK) and the dependent variable is the Economic Growth Rate. This research uses secondary data in the form of a time series, namely a 10 year time series, namely from 2014-2023. Data obtained from BPS Indonesia, and BI. The research method is quantitative with data analysis used by researchers, namely classical assumption tests (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression and statistical tests (coefficient of determination test (R2), t test and F test) with using eviews-10. The results of the partial regression coefficient (t test) show that the Human Development Index (HDI) has no effect on the Economic Growth Rate, nor does the Open Unemployment Rate variable have a significant influence on the Open Unemployment Rate variable on the Economic Growth Rate and is in line with the Poverty Rate variable (TK) that there is no significant influence of the Poverty Level variable on the Rate of Economic Growth. The results of the F test analysis show that there is no joint influence on the rate of economic growth on the island of Kalimantan.